Pengaruh Celebrity Endorser Dan Pengulangan Pesan Iklan terhadap Pembelajaran Konsumen - Christin Rosdiana Ngongo; Tumpal Pangihutan Situmorang (Universitas Kristen Wira Wacana Sumba, 2015)
In this globalization era, consumers have more and wide knowledge about products. It is therefore necessary for marketing strategy. One of the mixed marketing elements, that is, promotion that leads someone or organization to do an act of exchange in marketing so that it becomes a benchmark for the company to meet its needs and desires of its consumers and the use of celebrity in marketing communication. It is expected to help brand awareness, brand recognition, brand recall, and increasing brand purchase of a product.Research methods Non probability sampling with purposive sampling and data collection by using questionnaires. The analysis result shows that the Celebrity Endorser and repetition of advertising messages have a significant influence on the learning process of consumers. Keywords: Celebrity Endorser, Repetition Message Advertising, Consumer Education